Funerary dining or offerings for the dead? An archaeobotanical analysis of remains from shaft tombs in Petra, Jordan. (2nd January 2022) - Ramsay, Jennifer; Perry, Megan
Abstract : Ancient literary sources from the Hellenistic and Roman world describe the wide-spread practices of funerary feasting and supplying offerings for the deceased. However, the funerary customs of the Nabataeans are still not clearly understood within this broader cultural sphere. Evidence for feasting in Nabataean mortuary contexts largely relies on ceramic and faunal remains but rarely are plant remains included in these analyses. This paper presents archaeobotanical evidence from Nabatean-period tomb deposits from Petra, Jordan, to highlight the role plants played in this type of ritual context. Analysis of samples taken from eight rock-cut shaft tombs, excavated over three seasons (2012, 2014 and 2016), on the North Ridge of Petra, indicates the presence of a variety foodstuffs such as Triticum sp. (wheats), Hordeum vulgare (barley), Lens culinaris (lentil), Vitis vinifera (grape), Ficus carica (fig), Olea europaea (olive) and Phoenix dactylifera (date). These finds provide intriguing evidence of plants consumed or used as offerings during funerary ritual events. This study, in association with the analysis of bioarchaeological remains and ceramics expands our knowledge of Nabataean funerary practices and contributes to a broader understanding of the role of plants in ritual funerary events in the ancient world.